Thermal comfort of people in the hot and humid area of China-impacts of season, climate, and thermal history - Zhang, Y.; Chen, H.; Wang, J.; Meng, Q. (Indoor air, 2016)
We conducted a climate chamber study on the thermal comfort of people in the hot and humid area of China. Sixty subjects from naturally ventilated buildings and buildings with split air conditioners participated in the study, and identical experiments were conducted in a climate chamber in both summer and winter. Psychological and physiological responses were observed over a wide range of conditions, and the impacts of season, climate, and thermal history on human thermal comfort were analyzed. Seasonal and climatic heat acclimatization was confirmed, but they were found to have no significant impacts on human thermal sensation and comfort. The outdoor thermal history was much less important than the indoor thermal history in regard to human thermal sensation, and the indoor thermal history in all seasons of a year played a key role in shaping the subjects' sensations in a wide range of thermal conditions. A warmer indoor thermal history in warm seasons produced a higher neutral temperature, a lower thermal sensitivity, and lower thermal sensations in warm conditions. The comfort and acceptable conditions were identified for people in the hot and humid area of China.